Sm-Nd AND Rb-Sr AGES OF GARNET-BEARING GRANITE FROM THE SØR RONDANE MOUNTAINS, EAST ANTARCTICA - カガミ, ヒロオ; シライシ, カズユキ; KAGAMI, Hiroo; SHIRAISHI, Kazuyuki (National Institute of Polar Research, 1993)
P(論文) New Sm-Nd and Rb-Sr data are reported for the garnet-bearing biotite granite dike from the northwestern part of the Brattnipene area, Sør Rondane Mountains (71°52.5'S, 24°11'E). The mode of occurrence suggests that the granite intruded during the waning stage of the granulite facies regional metamorphism. The Sm-Nd whole-rock-mineral (biotite, plagioclase and garnet) isochron yields 1116±35Ma (MSWD=0.52) with an initial ratio of 0.511618±0.000056 (εNd=+8.2). The isochron is largely controlled by garnet. The calculation based on garnet and whole-rock pair shows 1118Ma. Biotite and plagioclase plot slightly away from the 1118Ma isochron. In the Rb-Sr system, no meaningful isochron for the whole-rock and three minerals can be drawn due to isotopic scatter. The whole-rock and plagioclase pair and the whole-rock and biotite pair yield 560Ma and 496Ma, respectively. The whole-rock and garnet pair cannot be calculated because of low concentration of Rb and Sr in garnet. The Sm-Nd age of 1118Ma is attributed to the age of the granite formation. This age is conformable with the Sm-Nd whole-rock isochron age of 961±101Ma for granulites from the nearby area reported by K. SHIRAISHI and H. KAGAMI (Recent Progress in Antarctic Earth Science, ed. by Y. YOSHIDA et al. Tokyo, Terra Sci. Publ., 29,1992). In addition Rb-Sr mineral ages of 560Ma and 469Ma for the granite are in good agreement with those of 560Ma (whole-rock, hornblende and plagioclase) and 490Ma (whole-rock and biotite) for the granulites. departmental bulletin paper